The effect of the opposite approach is to develop psychological security Students have a preparatory school - Kasem Reshan, Hamed (Al-Adab Journal, 2019)
The current research aimed to identify the effect of the opposite approach in developing the psychological security of students in the preparatory stage. For testing the hypotheses, the researcher used experimental design with the control group. The study population consisted of (460) students. The sample consisted of (20) students of the preparatory stage and distributed equally in two groups (experimental and experimental). To achieve the research objectives and test hypotheses, the researcher constructed a security measure Psychological (38) paragraph distributed on (4) areas (sense of personal security) (feeling of reassurance about the future) (sense of economic security) (sense of social security), as well as the construction of a program of guidance in accordance with the method of the opposite intention and the reality of (12) A follow-up session followed the researcher's scheme (Al-Dosari, 1985) to construct the Gel scheme S program beacon. .The results of the study showed statistically significant differences between the scores of the experimental group members in the tribal and remote tests on the psychological security scale. There were no statistically significant differences between the average grade of the control group members in the tribal and remote tests on the psychological security scale and the existence of statistically significant differences between the grades of the experimental group and the control group in the post-test on the psychological security scale. Based on the results of the research, the researcher made a number of recommendations, including: Teachers and teachers to instill confidence and hope in their students to contribute to raising their psychological security, and the need for periodic and continuous measurement of students to identify the levels of psychological security and holding seminars and seminars on the subject of psychological security for students in All stages of study, as well as the adoption of the current program and its application to students after the stability of its effectiveness in the development of psychological security. The researcher developed a number of proposals that may contribute to solving the problem of low psychological security, such as: the preparation of guidance programs based on cognitive and behavioral theories in the adjustment of psychological security in different stages of study and different samples, and conducting a correlation between the sense of psychological security and methods of parenting or cruelty by Teachers, as well as conduct a study of the correlation between the sense of psychological security and the possibility of aversion or compromise.